2017
DOI: 10.3390/medicines4030049
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil from Piper aduncum: Chemical Analysis, Antimicrobial Assessment, and Literature Review

Abstract: Background: The challenge in antimicrobial chemotherapy is to find safe and selective agents with potency that will not be compromised by previously developed resistance. Terrestrial plants could provide new leads to antibacterial, antifungal, or antiprotozoal activity. Methods: The essential oil (EO) of Piper aduncum L. (Piperaceae) from Cuba was analyzed by gas chromatography—mass spectrometry (GC-MS). A cluster analysis of P. aduncum EO compositions reported in the literature was carried out. The EO was scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 46 publications
2
40
0
4
Order By: Relevance
“…It has been known that Piper aduncum is an important Piperaceae, since several studies found in the literature have shown its potential as a great producer of EOs with therapeutic properties. 16 Therefore, this study aimed at developing biodegradable films made arrowroot starch into which EOs from Piper aduncum leaves and inflorescences were incorporated, at determining some of their physicochemical properties and at investigating their antifungal activity against Rhizopus microsporus and Colletotrichum gloeosporioides.…”
Section: Introductionmentioning
confidence: 99%
“…It has been known that Piper aduncum is an important Piperaceae, since several studies found in the literature have shown its potential as a great producer of EOs with therapeutic properties. 16 Therefore, this study aimed at developing biodegradable films made arrowroot starch into which EOs from Piper aduncum leaves and inflorescences were incorporated, at determining some of their physicochemical properties and at investigating their antifungal activity against Rhizopus microsporus and Colletotrichum gloeosporioides.…”
Section: Introductionmentioning
confidence: 99%
“…The species Piper aduncum L., popularly known as spiked pepper, has organic compounds with antifungal action which act on the elimination of skin and hair diseases (Monzote, Scull, Cos, & Setzer, 2017). It has a stimulating action for digestion, liver and healing (Maia et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It may be evidence of the existence of a new chemotype of the species P. aduncum in the southeast of Goiás state, Brazil. In addition, a recently published study describes nine different chemotypes of the species P. aduncum and a new one that was found in Cuba (Monzote et al 2017). In the essential oil of aerial parts of P. aduncum in Cuba, the following major constituents were identified: piperitone (23.7%), camphor (17.1%) and viridiflorol (14.5%) (Monzote et al 2017).…”
Section: Resultsmentioning
confidence: 99%